Reformulation of Crop and Management Factor in ANSWERS model - Hidayat, Yayat; Sinukaban, Naik; Pawitan, Hidayat; Murtilaksono, Kukuh (UNIVERSITY OF LAMPUNG, 2008)
Crop and management factor value is significantly corelated with outputs of ANSWERS model especially on soil erosion. Using daily crop and management factors (daily C factors), the ANSWERS model performs well in predicting soil erosion which is showed by determination coeffient (R2 = 0.89), model efficiency (0.86), and average of percentage model deviations (24.1 %). Whereas using USLE C factor (2 cropping systems), predicted is much higher than measured soil erosion (over estimate). Output of the model is not statisfy, it is represented by model coefficient (0.40) and average of percentage model deviations (63.6 %).